Monitoring of Surgically Treated Upper Arm Fracture by Implanted Antenna at 402 MHz - Zeinelabedeen, Wael; Uyguroglu, Rasime (Mdpi, 2023)
Remote patient monitoring aims to reduce non-essential visits to clinics and hospitals, monitor high-risk patients outside clinical settings, and optimize clinical staff utilization. This paper proposes a new monitoring application for surgically treated upper arm fractures. The humerus fracture should be healed within four to six weeks. Traditional monitoring is conducted through repeated X-ray images and visits to clinical laboratories or hospitals. Our goal is to avoid the expected drawbacks due to repeated exposure to X-rays, such as vomiting, bleeding, fainting, and sometimes the risk of cancer. Furthermore, this study aims to improve the patient's quality of life during the treatment period by monitoring them at home. The technique depends on implanting a 116 mm length half-wave dipole antenna in the fractured arm and recording the reflection coefficient and the transmitted power at the far-field of it outside the body at 402 MHz. The fracture is represented by an extra layer added to the humerus, which increases the loss of electromagnetic field in the human tissue and then reduces the value of the transmitted power. The existence of fractures shows a change in the transmitted average power densities (APDs) in the range of 11.54% to 15.75%, based on the fracture types, and an increase in reflection coefficients in the range of -22.35 dB to -22.65 dB compared to the normal bone, which monitors the bone healing status. The standard limit of the specific absorption rate was taken into account to guarantee the safety of the human body. Different fracture types were considered and monitored, and CST Microwave Studio was used for simulation. The technique was verified experimentally by measurements carried out on a lifeless front leg animal model. The technique can also be used for the monitoring of ulna and tibia fractures.
Keywords: EM wave application; implanted antenna; healthcare monitoring; fracture healing; upper arm